Lactococcus lactis subsp. cremoris YRC3780 modifies function of mesenteric lymph node dendritic cells to modulate the balance of T cell differentiation inducing regulatory T cells - Nakagawa, Ryogo; Gu, Wenting; Mizobuchi, Hibine; Kodera, Shuhei; Takano, Tomohiro; Wang, Yimei; Fujioka, Ikumi; Uchida, Kenji; Nakajima-Adachi, Haruyo; Hachimura, Satoshi (Frontiers in Immunology, 2024)
Introduction The intestinal immune system plays a pivotal role in the induction of immune responses against food. In the case of T cell response, dendritic cells (DCs) are especially important. However, the regulation of immune responses to food by intestinal DCs has been poorly described. In this study, we analyzed the effect of Lactococcus lactis subsp. cremoris YRC3780, a lactic acid bacterial strain isolated from kefir, a traditional fermented milk product, on the immune responses induced by antigen presentation by intestinal DCs to T cells as well as the mechanism of action of these immunomodulatory effects. It has been shown that L. cremoris YRC3780 ameliorates the symptoms of pollinosis in both animal and human studies. Methods CD11c+ cells from mesenteric lymph nodes (MLNs) of BALB/c mice were cultured as MLN DCs with L. cremoris YRC3780 and expression of genes inducing regulatory T cells (Tregs) was examined by qPCR. In addition, MLN DCs were cocultured with CD4+ T cells from DO11.10 transgenic mice expressing an ovalbumin (OVA)-specific TCR and the OVA antigen peptide and L. cremoris YRC3780. Induction of Tregs was examined by flow cytometry, gene expression was analyzed by DNA microarray and qPCR, and the production of cytokines was measured by ELISA. MLN DCs from TLR2-deficient mice and components of L. cremoris YRC3780 were used to examine the recognition of YRC3780 by MLN DCs. Results L. cremoris YRC3780 enhanced the expression of genes involved in Treg induction in MLN DCs and induced Foxp3+CD4+T cells in an MLN DC and CD4+ T-cell co-culture system. The effect on MLN DCs was likely mediated by receptors other than TLR2. Together with microarray analyses of CD4+ T cell gene expression and cytokine ELISA, it was demonstrated that L. cremoris YRC3780 promoted the induction of Th1 and Tregs, and regulated the balance of Th1/Th2 and Treg/Th17 cells involving multiple genes via the antigen-presentation of MLN DCs. Discussion Our findings provide insights into the modulation of intestinal immune responses mediated by DCs and the antiallergic effects of lactic acid bacteria.